Trends and issues in multicultural business communications in South A'frica - R Hugo-Burrows Hugo-Burrows (Communicare)
In South Africa we have lived in a society where separation of communities and racial groups has been the norm. Since 1994 the separation is being bridged as more individuals encounter people with different attitudes, value systems and cultural behavioural patterns in social and business environments. This leads to new avenues of understanding, but also to a wider scope for misunderstanding and unintentional miscommunication, especially in the business context. The way in which people communicate in a business setting, varies from culture to culture. Such variation occurs in all stages of development and at all levels of culture. whether from one corporate culture to another, or from one region, state or country to another. Although most rules of business communication apply to the domestic business environment, Intercultural business communication requires knowledge and skills that differ from those within a specific culture. It is impossible to know all the variations in business communication in a multicultural business society like South Africa, but businesspeople can and should prepare themselves for those experiences they are most likely to face in employee and customer relations when conducting business in more than one culture. This article probes the possibility of diminishing business miscommunication in South Africa, by focussing on awareness of barriers to multicultural marketing and management communication. Business communication is defined as consisting of management as well as marketing communication. A pilot survey on existing business communication strategies in a large South African province is discussed. This has pointed towards a more comprehensive research project, with